Breeding in Africa for Africa - International Potato Center (2011)
The first batch of sweetpotato varieties produced using the new accelerated breeding method were released in February 2011 in Mozambique. This method will speed up the rate at which new improved preferred varieties reach farmers and consumers. Experiments have confirmed the existence of exploitable heterosis for use in sweetpotato breeding, which could substantially boost sweetpotato yields.